Preparation and property study of sawdust-modified cement mortar - Cheng, Yu; Liu, Jiatao; Wang, Wentong; Jin, Lu; Yan, Shiying (Frontiers in Materials, 2024)
Sawdust, a solid waste generated during stone processing, poses a serious threat to the environment with its untreated accumulation. This study aims to explore the application of sawdust as a modifier in cement mortar to improve its mechanical properties and durability, while promoting the green and sustainable development of building materials. This paper first analyzes the chemical composition and physical properties of sawdust, and discusses its mechanism of action in cement mortar. By systematically optimizing the blending ratio and modification method of sawdust, the sawdustmodified cement mortar with excellent performance was prepared. This study evaluates the key performance indicators of sawdust-modified cement mortar, such as compressive strength, flexural strength, and durability, through a series of experiments. The experimental results indicate that the incorporation of an appropriate amount of sawdust significantly enhances the mechanical properties of cement mortar, while also improving its durability, particularly in terms of freeze-thaw resistance. Microstructural analysis reveals the mechanism by which sawdust improves the pore structure of cement mortar; the active components in the sawdust react with the hydration products of cement, resulting in the formation of crystalline structures with higher strength.